Exploiting supramolecular chemistry in metal recovery: novel zwitterionic extractants for nickel(II) salts - Akkus, N; Campbell, JC; Davidson, J; Henderson, DK; Miller, HA; Parkin, A; Parsons, S; Plieger, PG; Swart, RM; Tasker, PA; West, LC (ROYAL SOC CHEMISTRY, 2003)
Hexadentate tris-salicylaldimine ligands bearing ortho-N-dialkylaminomethyl substituents have been shown to function as ditopic ligands for NiSO4 or NiCl2. The incorporation of the Ni-ion into the N3O33- site templates the pendant alkylammonium groups to allow them to hydrogen bond to the attendant anion(s). Formulation as complexes of the trianionic/tricationic ligand is supported by X-ray structure determinations of solvated forms of the complexes [Ni(L)SO4] and [Ni(L)Cl]Cl, where L = tris-1,1,1-{2-hydroxy-3-(piperidin-1-ylmethyl)-5-tert-butyl-benzaldiminomethyl} ethane. The kerosene-soluble ligand, tris-2,2',2-{2-hydroxy-3-(di-n-hexylaminomethyl)-5-nonylbenzaldiminomethyl} amine, functions as a good extractant for nickel salts, showing high selectivity for recovery of NiCl2 over NiSO4. This reagent can be stripped and recycled directly using aqueous ammonia or by first displacing the Ni2+ with acid and then neutralising the pendant alkylammonium groups. The acid-stripping is accompanied by hydrolytic degradation of the reagent, but in many other respects this novel class of reagent shows promise in opening up novel flowsheets for nickel recovery, based on transport of the metal salt as opposed to ion-exchange based processes.
Keywords: SOLVENT-EXTRACTION; PYRIDINECARBOXYLATE ESTERS; SYNERGISTIC MIXTURES; CHLORIDE MEDIA; HYDROCHLORIC-ACID; MIXED EXTRACTANT; AQUEOUS-SOLUTION; DITOPIC LIGANDS; COPPER; SEPARATION; Chemistry